2014
DOI: 10.2478/cer-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Labour Market Developments in the Maritime Industry of the South Baltic Region

Abstract: There are two aims of this study. The first is to outline the developments in the maritime economy and employment in the South Baltic Region, and the second to identify the emerging activities in the maritime industry and to reveal the prospects and potential for labour market development, taking into account the demand for labour, required professions, qualifications of the labour force, and feasible cross-border mobility. This comparative study refers to four EU Baltic coast regions, namely the Meckl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Economic development of the region's development guidelines coastal districts in Garut district concluded that the priority of economic development is mainly directed to agriculture, manufacturing, trade, hotel and restaurant sector, gas, electricity and drinking water. In which areas have the opportunity and authority to make policies that correspond to the potential of the area in order to accelerate the economic development of the region to improve the welfare of society (Bernacki, 2014).…”
Section: Results Analysis Of Sea Transport Sector Sub District/city Ofmentioning
confidence: 99%
“…Economic development of the region's development guidelines coastal districts in Garut district concluded that the priority of economic development is mainly directed to agriculture, manufacturing, trade, hotel and restaurant sector, gas, electricity and drinking water. In which areas have the opportunity and authority to make policies that correspond to the potential of the area in order to accelerate the economic development of the region to improve the welfare of society (Bernacki, 2014).…”
Section: Results Analysis Of Sea Transport Sector Sub District/city Ofmentioning
confidence: 99%
“…Maritime sociology in Poland faced crisis similarly to the Polish maritime industry during the two decades of the transformation period , but during the last decade, Polish sociologists introduced the sessions of this subdiscipline to the European Sociological Association congresses (Lisbon 2009, Geneve 2011, Torino 2013, Prague 2015, Manchester 2019) as well as to the national sociology congresses in Poland (Szczecin 2013, Gdansk 2016, Wrocław 2019) and Germany (Trier 2015). In the recent decades, the changing conditions of the maritime economy workers have been increasingly frequently analyzed not only by logisticians, safety specialists (in terms of both individual safety and the protection of maritime interests [25]), and economists [2], [4], [12] but also by sociologists [13], [15], [16].…”
Section: Introductionmentioning
confidence: 99%